Excavation of 45-47 Gallowgate, Aberdeen - Murray, Hilary (Proceedings of the Society of Antiquaries of Scotland, 1985)
Fifteen phases of occupation on the western route to the medieval burgh indicate the changing status from 13th to 19th century. Pottery sequence confirms another from Aberdeen.